First occurrence of Rift Valley fever outbreak in Niger, 2016. Issue 1 (9th November 2018) - Lagare, Adamou; Fall, Gamou; Ibrahim, Alkassoum; Ousmane, Sani; Sadio, Bacary; Abdoulaye, Mariama; Alhassane, Abdou; Mahaman, Ali Elh; Issaka, Bassira; Sidikou, Fati; Zaneidou, Maman; Bienvenue, Baruani; et al.
Abstract: Rift Valley fever (RVF) is a mosquito‐borne viral zoonosis causing abortions and high mortality among animals, whereas in humans, the disease is usually mild or asymptomatic. In September 2016, the Republic of Niger declared the first RVF outbreak in the northern region of Tahoua near the Malian border. This study describes the outbreak and reports the results of serological and molecular investigations of the human and animal samples collected. Serum samples from both human and animal suspected cases have been confirmed at the Centre de Recherche Médicale et Sanitaire (CERMES) and the Laboratoire Centrale d'Elevage (LABOCEL) public health and animal reference laboratories, respectively. Techniques for biological confirmation were real time reverse transcription polymerase chain reaction (RT‐PCR) and enzyme linked immunosorbent assay (ELISA). Phylogenetic trees were established after genetic sequencing of the small and medium segments of the RVF virus (RVFV) genome. Out of the 399 human samples collected, 17 (4.3%) were confirmed positive for RVFV. Overall, 33 (8.3%) deaths occurred out of which five (29%) were among the 17 confirmed cases. Regarding animals, 45 samples were tested, three of which were RT‐PCR positive and 24 were IgG positive. The phylogenetic analyses showed that the Niger strains clustered with Senegal 2013 and Mauritania 2015 RVFV strains. This first outbreak of RVF was very challenging for public and animal health laboratories in Niger. Besides resulting in human deaths, important loss of cattle has been reported. Therefore, vigilance has to be strengthened emphasising vector control strategies and active surveillance among animals. Abstract : RVF outbreak in Niger, 2016. The phylogenetic analyses of strains showed similarities with Senegal 2013 and Mauritania 2015 RVFV strains.